Genomic Characterization of Multidrug-Resistant Enterobacteriaceae Clinical Isolates from Southern Thailand Hospitals: Unraveling Antimicrobial Resistance and Virulence Mechanisms - Thunchanok Yaikhan; Sirikan Suwannasin; Kamonnut Singkhamanan; Sarunyou Chusri; Rattanaruji Pomwised; Monwadee Wonglapsuwan; Komwit Surachat (MDPI AG, 2024)
The emergence and spread of antimicrobial resistance (AMR) among Enterobacteriaceae pose significant threats to global public health. In this study, we conducted a short-term surveillance effort in Southern Thailand hospitals to characterize the genomic diversity, AMR profiles, and virulence factors of Enterobacteriaceae strains. We identified 241 carbapenem-resistant Enterobacteriaceae, of which 12 were selected for whole-genome sequencing (WGS) and genome analysis. The strains included Proteus mirabilis, Serratia nevei, Klebsiella variicola, Klebsiella aerogenes, Klebsiella indica, Klebsiella grimontii, Phytobacter ursingii, Phytobacter palmae, Kosakonia spp., and Citrobacter freundii. The strains exhibited high levels of multidrug resistance, including resistance to carbapenem antibiotics. Whole-genome sequencing revealed a diverse array of antimicrobial resistance genes (ARGs), with strains carrying genes for ß-lactamase, efflux pumps, and resistance to other antibiotic classes. Additionally, stress response, metal tolerance, and virulence-associated genes were identified, highlighting the adaptability and pathogenic potential of these strains. A plasmid analysis identified several plasmid replicons, including IncA/C2, IncFIB(K), and Col440I, as well as several plasmids identical to those found globally, indicating the potential for the horizontal gene transfer of ARGs. Importantly, this study also identified a novel species of Kosakonia spp. PSU27, adding to the understanding of the genetic diversity and resistance mechanisms of Enterobacteriaceae in Southern Thailand. The results reported in this study highlight the critical importance of implementing effective antimicrobial management programs and developing innovative treatment approaches to urgently tackle AMR.